Normative workload on physicians of ophthalmological in-hospital departments of intensive care hospital, depending on the volume of work performed - Ginzburh V.H.; Lekhan V.M.; Lamza O.Ye. (Medičnì Perspektivi)
The research was done with the application of “Methodology of definition of normative workload of physicians of in-hospital departments of intensive care hospitals” approved by the Ministry of health care of Ukraine on the basis of two ophthalmological departments of hospital N 8 in Dniptropetrovsk, where a routine and urgent intensive and secondary care of ophthalmological profile is provided in twenty-four-hour regime. Normative workload of ophthalmologists is substantiated coming from on the number of cured patients and number of surgeries per year.